The role of decision making and resources in group solutions of a problem involving Bayes’ formula - Stillman, Gloria (NOMAD Nordic Studies in Mathematics Education, 2005)
This study was concerned with the decision making behaviour of students at the upper secondary level of schooling. Transcripts of verbal reports produced by student pairs solving a probability problem involving Bayes’ Formula were analysed using Schoenfeld’s protocol parsing scheme. The students’ monitoring and decision making were significant contributors to how solutions evolved but so too were particular words in the problem statement. Both the quality of control behaviour and students’ resources contributed to the success or otherwise of their solution. Resource-related factors included misinterpretation of the problem, misreading of the problem, failure to make the connections between probability rules and their conditions of use, and confusion between compound and conditional probability.